Pengaruh Kualitas Pelayanan, Harga, Dan Lokasi Terhadap Kepuasan Pelanggan Di Flame Bar Seminyak Badung - Arcana, Kadek; Sutapa, I Ketut; Kartimin, I Wayan (Jurnal Mosaik Hospitaliti, 2023)
This study aims to determine the effect of service quality, price, location on  customer satisfaction. The population in this study were Flame Bar Seminyak Badung customers with a sample of 100 respondents. The data analysis technique used in this study is multiple linear regression. Based on the results of the study it can be seen that the quality of services has a positive and significant effect on customer satisfaction, price has a significant positive effect on customer satisfaction, location has a positive effect significantly to customer satisfaction, service quality, price, location has a positive and significant effect on customer satisfaction, the magnitude of the influence of service quality, price, location on customer satisfaction is 65.9% and the service quality variable has a more dominant influence on customer satisfaction. Suggestions that can be given by researchers are Flame Bar Seminyak Badung is expected to provide training to employees, make competitive price policies, make signboards or directions that can be seen clearly from a far.